New IEC Standards Requirements to the Parameters of Powerful Electromagnetic Pulsed Disturbances - Kravchenko, V.I.; Knyazyev, V.V.; Koliushko, G.M.; Vavriv, L.V. (Радиофизика и радиоастрономия, 2002)
The European Union Directive on EMC defines a new concept of providing electromagnetic compatibility. The Directive mandates that all electromagnetic phenomena which can influence the operation of technical devices need to be considered. Electromagnetic phenomena which accompany high-altitude nuclear explosions are now on the list of standardized powerful electromagnetic pulsed disturbances which previously included only lightning and electrostatic discharges. The purpose of this paper is to familiarize the developers of the electronic, radio electronic and electrical products with the new EMC requirements set to those products.